Analysis of Er3+ incorporation in SnO2 by optical investigation - Morais,Evandro A. de (2006)
Er3+ emission in the wide bandgap matrix SnO2 is observed either through a direct Er ion excitation process as well as by an indirect process, through energy transfer in samples codoped with Yb3+ ions. Electron-hole generation in the tin dioxide matrix is also used to promote rare-earth ion excitation. Photoluminescence spectra as function of temperature indicate a slight decrease in the emission intensity with temperature increase, yielding low activation energy, about 3.8meV, since the emission even at room temperature is rather considerable.